Retail supply chain management - Ayers, James B; Odegaard, Mary Ann (Series on resource management, 2008)
Most retail industry managers focus on products instead of operations. This book demonstrates the connection between products, market, and strategies. It provides an understanding of each facet of the supply chain to show how each component is related and can be manipulated for maximum return.